Role of TRIM24 in the regulation of proteasome-autophagy crosstalk in bortezomib-resistant mantle cell lymphoma - Bouvier, Corentin (2025)
Funding Information: GR received research funding from TG Therapeutics and Kancera, to support studies unrelated to the present work. MSR is scientific director of BMolecular and does not receive any economic compensation. Funding Information: This work was supported by the UbiCODE project funded by the EU\u2019s Horizon 2020 research and innovation program under the Marie Sk\u0142odowska-Curie grant agreement No 765445, the Telethon grant number 23115, the JANUS (ANR-23-CE13-0013), the ERMMIT (ANR-24-CE44) the CONACyT-SRE (Mexico) grant 0280365, the Fondation Toulouse Cancer Sant\u00E9 (PROTRIM project) and the REPERE and pr\u00E9maturation (ubipi\u00E8ges) programs of Occitanie. The authors also acknowledge the financial support from Fondo de Investigaci\u00F3n Sanitaria PI18/01383, European Regional Development Fund (ERDF) \u201CUna manera de hacer Europa\u201D (to GR). MA was a fellow of PROTEOblood (EFA360/19), a project co-financed by the ERDF through the Interreg V-A Spain-France-Andorra (POCTEFA) program. This work was carried out, in part, under the CERCA Program (Generalitat de Catalunya). CB received support from the ARC foundation (ARCDOC42023010005996) and La ligue contre le Cancer (TAJV22303). WX received support from Consejo Nacional de Ciencia y Tecnolog\u00EDa (CONACYT) grant CB-2017-2018-A1-S-22895. RB and JDS acknowledge MCIN/AEI/10.13039/501100011033 (PID2020-114178GB-I00, PID2023-147399NB-100 and CEX2021-001136-S Severo Ochoa Excellence Program). RF is supported by grant PID2022-139691OB-I00 funded by MCIN/AEI/10.13039/501100011033 and ERDF A way of making Europe (European Union). Funding Information: We do thank all members of UbiCARE and Rosas Barrio\u00B4s Laboratory and Olivier Coux for technical help and advice. We thank the COST Action CA20113 \u2018PROTEOCURE\u2018 supported by COST (European Cooperation in Science and Technology). Publisher Copyright: © The Author(s) 2025.